A Case Report: Intracranial Bleeding Due to Vitamin K Deficiency - Inggrit Anggraini; Dwi Antika Sari (The International Science of Health Journal, 2024)
Vitamin K deficiency bleeding is a pediatric bleeding disorder caused by a lack of vitamin K. Vitamin K deficiency causes coagulation disorders that can manifest clinically as bleeding. Vitamin K is a fat-soluble vitamin that is needed in the activation of procoagulant factors II, VII, IX, and X and anticoagulant proteins C and S. We report a case of a 2-month-old baby brought by his mother to Dr. Suhatman Hospital, MARS with complaints of fever accompanied by seizures for more than 10 minutes, the left side of the body felt stiff, the eyes moved and looked up, and the seizures recurred and the patient's umbilicus bled. After alloanamnesis, physical examination and supporting examinations, the patient was diagnosed with late-onset vitamin K deficiency.